MARKETING MIX TERHADAP PURCHASE INTENTION PADA PRODUK R&B TEA SUMMARECON MALL SERPONG - Fadhulloh, Fariz Alaudin; Widiati, Euis (LPPM STIE YKPN Yogyakarta, 2023)
Marketing mix strategy is one of the business strategies implemented by companies to attract consumer purchase interest in order to sustain their business. The marketing strategy consists of 7Ps (Product, Price, Promotion, Place, People, Process, Physical Evidence). The aim of this research is to determine the influence of marketing mix on consumer purchase interest in R&B Tea Summarecon Mall Serpong products. This research uses a quantitative research design. The population size in this study is 23,752 consumers, while the sample size is 100 respondents. The sampling technique used is purposive sampling. The primary data used in this study is a questionnaire survey distributed using Google Form to 100 individuals who have consumed R&B Tea Summarecon Mall Serpong products. Hypothesis testing is conducted using simple linear regression analysis, and the research findings reveal that the marketing mix has a positive influence on consumer purchase interest.